Ouvidoria pública como instrumento de participação popular: uma proposta para o município de Uberlândia - Reis, Mariana Vidal (2023)
The Federal Constitution of 1988 values the citizen, guaranteeing him the right to popular participation and control. Ombudsmen are mechanisms that enable the exercise of these rights. However, for them to fulfill their public purpose of acting as a channel of dialogue between citizens and the State, facilitating and encouraging popular participation and control, it is relevant that said bodies have certain characteristics in their institutional design and conditions to account for its actions. In this area, the Comptroller General of the Union developed the Public Ombudsman Maturity Model - MMOuP, which seeks to help the implementation process and promote improvements in the management of ombudsmen. Based on ideal ombudsman and MMOuP models, this research aimed to evaluate the performance of the Ombudsman in the municipality of Uberlândia, in order to identify whether it can be considered an instrument of popular participation and control, suggesting referrals. The research has a qualitative approach and, as for the purposes, it presents characteristics of descriptive, exploratory and explanatory research. The type of research adopted in this work was the single case study, with data collection from documental analysis of primary and secondary data and participant observation. Data were interpreted using the content analysis technique. The results lead to the conclusion that the Uberlândia Ombudsman is not fully institutionalized. In addition, the results indicate a low publicity to the community of the existence of the Ombudsman, its attributions and results, which undermines its status as an instrument of popular participation and control. Due to the reflections, an Executive Summary was produced as technological products of this dissertation with the main results and suggestions for improving the ombudsman; and course plan for holding a lecture, in order to collaborate with the institutionalization and achievement, by the Ombudsman of the municipality of Uberlândia, of the condition of instrument of control and popular participation